The Role of the Aryl Hydrocarbon Receptor in Vascular Factors Related to Preeclampsia in a Smoking Mouse Model - Ho-Yeon Kim; Ye-Seon Seok; Hye-Yeon Moon; Geum-Joon Cho; Ki-Hoon Ahn; Soon-Cheol Hong; Min-Jeong Oh; Hai-Joong Kim (Current Issues in Molecular Biology, 2024)
Smoking cigarettes is known to lower the risk of preeclampsia. The objective of this study is to evaluate the effect of smoking on the expression of soluble FMS-like tyrosine kinase-1 (sFlt-1), vascular endothelial growth factor (VEGF), and endoglin (sEng)-1 and the role of the aryl hydrocarbon receptor (AhR) in pregnant mice. We developed a smoking mouse model using a gas-filling system. One or two cigarettes per day were exposed to each of the five pregnant mice for five days a week throughout pregnancy. AhR agonist and antagonist were injected. Serum levels and expression in the placenta of sFlt-1, VEGF, and sEng-1 were analyzed and compared among the cigarette smoke and no-exposure groups after delivery. Compared to the no-smoke exposure group, the serum level of sFlt-1 was significantly decreased in the two-cigarette-exposed group (p < 0.001). When the AhR antagonist was added to the two-cigarette-exposed group, sFlt-1 levels were significantly increased compared to the two-cigarette group (p = 0.002). The levels of sFlt-1 in the AhR antagonist group did not change regardless of two-cigarette exposure (p = 0.064). With the AhR agonist, sFlt-1 decreased significantly compared to the control (p = 0.001) and AhR antagonist group (p = 0.002). The sFlt-1 level was significantly decreased after the injection of the AhR agonist compared to the control group (p = 0.001). Serum levels of VEGF were significantly decreased in the one-cigarette-exposed group compared to the control group; however, there was no difference between the control and the two-cigarette-exposed groups. The placental expression of sFlt-1, VEGF, and sEng were inconsistent. This study offers insights into the potential role of AhR on antiangiogenic sFlt-1 associated with preeclampsia. It may support the invention of a new treatment strategy for preeclampsia using AhR activation.